Development of Material Teaching of Health in Physical Education Classes for Students in Elementary School (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The results of field observations have not found any teaching materials that are devoted to health education materials in the lower grades of elementary school. This study aims to produce a product of teaching materials for health education materials to be implemented in physical education subjects, sports and health for low grade elementary school levels. The research method used is research development or Research & Development. The product development process has the following steps; (1) Needs analysis, (2) Preparation of initial product draft, (3) Validation by experts, (4) Revision of initial product draft, (5) Product trial, (6) Product revision, (7) Product feasibility test, (8) Final product revision, (9) Final product. The instrument in this study was using a questionnaire. The result of expert validation from the initial product draft was 79.7%. The results of the analysis of the product feasibility assessment in the first product trial was 87.6%. The product trial II received an assessment of 87.3%, and the feasibility test received a percentage rating of 86.7%. The results of the analysis in terms of product acceptability in the first product trial were 87.6%. The product trial II got a percentage value of 87.3%, and the feasibility test got a percentage value of 86.7%. The conclusion is that the product development of health education teaching materials is appropriate to be used in the implementation of physical education subjects, sports and health in health education materials for students in grades I, II, and III at the elementary school level.